2001
DOI: 10.1023/a:1022288022969
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: It has long been known that cancer cells often express more heavily sialylated glycans on their surface and that this feature sometimes correlates with invasion. It is now well established that specific sialylated structures, such as the Thomsen-Friedenreich-related antigens, the sialyl Lewis antigens, the sialyl alpha2-6 lactosaminyl structure, the polysialic acid or some gangliosides, can mediate cellular interactions and are altered in cancer cells. This review summarizes the current knowledge on the cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
107
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(108 citation statements)
references
References 140 publications
1
107
0
Order By: Relevance
“…Proteolytically untethered ST6Gal-1 is subsequently released into systemic circulation, where it has been generally regarded as a by-product of metabolic inefficiency without significant physiologic function, although circulatory ST6Gal-1 activity also increases during the acute phase response (6 -8, 16). Despite a lack of understanding for the physiologic function of the circulatory sialyltransferase, there have been numerous reports strongly correlating serum ST6Gal-1 with pathologic conditions, such as cancer (17). Elevated circulatory ST6Gal-1 activity has been associated with disease severity and poorer prognosis in oral and breast cancers (18,19).…”
mentioning
confidence: 99%
“…Proteolytically untethered ST6Gal-1 is subsequently released into systemic circulation, where it has been generally regarded as a by-product of metabolic inefficiency without significant physiologic function, although circulatory ST6Gal-1 activity also increases during the acute phase response (6 -8, 16). Despite a lack of understanding for the physiologic function of the circulatory sialyltransferase, there have been numerous reports strongly correlating serum ST6Gal-1 with pathologic conditions, such as cancer (17). Elevated circulatory ST6Gal-1 activity has been associated with disease severity and poorer prognosis in oral and breast cancers (18,19).…”
mentioning
confidence: 99%
“…Although altered glycoconjugates correlate with an increased propensity to liver metastasis in animal models [30], we failed to find a correlation with AJCC tumor classification. In some studies, α(2,6)-sialylation is negatively correlated with a good clinical outcome in CRC patients [18, 20, 28]. But in those studies the most widely used tool for the investigation of the sialyl-α(2,6)-linkage was Sambucus nigra agglutinin and this lectin not only recognizes the CDw75 antigen, but also recognizes the sTn epitope, another glycan structure highly expressed in colon cancer tissues that has also been related to patient survival [31].…”
Section: Discussionmentioning
confidence: 99%
“…In any case, a large percentage of primary and metastatic gastrointestinal carcinomas show increased activity with anti-CDw75 antibodies [32, 33] and elevation of ST6Gal I mRNA in colorectal tissues [34, 35] and in colorectal cancer cells [20] have also been related to the metastasis process. One possible explanation is connected with the nonadhesiveness of the cells [28], because it has been proposed that a process of selection for metastatic cells by hypersialylation of specific tumor cell surface glycoconjugates would promote the release of single cells from the primary tumor mass [20, 30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Fifteen or more human ST cDNAs have also been cloned and characterized based on their substrate specificities: ST3Gal I to V, ST6Gal I, ST3GalNAc I to VI, and ST8Sia I to V. Each of the ST genes is differentially expressed in a tissue-, cell type-, and stagespecific manner. 5) It has previously been reported that expression of FUT IV mRNA is moderately and ST3Gal I mRNA prominently increased in human colorectal cancer tissues 6,7) and that FUT III, FUT VI and ST3Gal IV are the most abundantly expressed and FUT IV, ST3Gal II, ST3Gal I and ST6Gal I are increased in colorectal carcinoma. 8) These reports have indicated that FUT III and IV and ST3Gal I and IV are mainly responsible for the biosynthesis of distal glycans such as Lewis-type antigens.…”
mentioning
confidence: 97%